Dve novi vrsti sovk v favni Slovenije: Eremobina pabulatricula (Brahm, 1791) in Euxoa segnilis (Duponchel, 1836) (Lepidoptera: Noctuidae) - Habeler, Heinz (Acta entomologica slovenica (Ljubljana), 2004)
In 2004 two Noctuidae species new to Slovenia were discovered. Eremobina pabulatricula (Brahm, 1791) was found near Ribnica in Dolenjsko and Euxoa segnilis (Duponchel, 1836) in Pragersko south of Maribor and in Črnotiče at the Karst edge.
Keywords: insekti; Lepidoptera; Slovenia; Slovenija; zoogeografija